Creep in steel-concrete composite beams bonded by adhesive and connected by studs - Li, Alex; Yurtdas, Ismail; Abbes, Boussad (Structures, 2025)
This study investigates the creep behavior of steel-concrete composite beams, comparing traditional shear stud connections with adhesive bonding. Unlike shear studs, adhesive bonding distributes stress more evenly along the interface, reducing stress concentrations and enhancing structural performance. It also eliminates the need for welding or bolting, significantly reducing construction time—an advantage particularly beneficial for prefabricated and modular structures. Flexural creep tests were conducted under constant loads for 120 days, with longitudinal deformations monitored. Three-dimensional finite element models incorporating linear viscoelastic theory were developed to analyze strain and stress evolution. Results highlight significant differences: adhesive-bonded beams exhibit lower creep strains and more uniform strain distribution compared to stud-connected beams. Creep strain follows a three-stage pattern: in the initial stage (0–9 days), adhesive bonding reduces the rate of creep increase by up to 39 %; in the second stage (10–80 days), by up to 33 %; and in the final stage, the creep stabilizes, with an overall reduction of up to 24 %. Finite element simulations further demonstrate that adhesive bonding enhances stress redistribution and ensures a more uniform creep variation along the beam’s length, offering a promising alternative for long-term structural performance.
Keywords: Adhesive; Composite beam; Creep; Finite element; Shear stud; Steel